A prospective study of vasculitis patients collected in a five year period: evaluation of the Chapel Hill nomenclature. Issue 6 (1st June 2000) - Sørensen, Søren Freiesleben; Slot, Ole; Tvede, Niels; Petersen, Jørgen
Abstract : OBJECTIVE: To test the usefulness of the Chapel Hill nomenclature, supplemented with surrogate parameters, as diagnostic criteria for primary vasculitides. METHODS: To prospectively evaluate vasculitis patients according to a standardised clinical and para-clinical programme. In accordance with the Chapel Hill publication surrogate parameters were used: proteinuria, haematuria and red blood cell casts (glomerulonephritis), angiographic or ultrasonic demonstration of aneurysms or stenoses (arteritis), radiological lung infiltrates or cavitations of more than one month's duration (granuloma in the lungs), bloody nasal discharge or crusts, chronic sinusitis, otitis and/or mastoiditis, bone and/or cartilage destruction, and acute hearing loss (granuloma in upper airways). RESULTS: The following entities were diagnosed: giant cell arteritis (n=14), Takayasu arteritis (n=1), polyarteritis nodosa (n=2), Wegener's granulomatosis (n=27), Churg-Strauss syndrome (n=2), microscopic polyangiitis (n=12), Henoch-Schönlein purpura (n=2), cutaneous leucocytoclastic angiitis (n=37), and secondary vasculitis (n=21). Giant cell arteritis and cutaneous leucocytoclastic angiitis were in all cases diagnosed by biopsy. Using the Chapel Hill nomenclature supplemented with surrogate parameters, only 8 of 27 patients were diagnosed with Wegener's granulomatosis, and 3 of 12 cases with microscopic polyangiitis. The number of patients in the remaining diagnostic entities were considered to few to evaluate. CONCLUSIONS: The Chapel Hill nomenclature, supplemented with surrogate parameters, failed to act as diagnostic criteria in Wegener's granulomatosis and microscopic polyangiitis. The following diagnostic criteria are proposed for Wegener's granulomatosis: (1) Biopsy or surrogate parameter for granulomatous inflammation in the respiratory system and (2) Biopsy verified necrotising vasculitis in small to medium sized vessels or biopsy/surrogate parameter for glomerulonephritis or positive PR3-ANCA test and (3) Lack of eosinophilia in blood and biopsy samples. The following diagnostic criteria are proposed for microscopic polyangiitis: (1) Biopsy verified necrotising vasculitis in small vessels and/or glomerulonephritis with few or no immune deposits and (2) Involvement of more than one organ system as indicated by biopsy verified vasculitis in small to medium sized vessels or surrogate parameter for glomerulonephritis and (3) Lack of biopsy and surrogate parameter for granulomatous inflammation in the respiratory system. Using these criteria all Wegener's patients and 9 of 12 patients with microscopic polyangiitis could be diagnosed.